PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL FLIPPED CLASSROOM PADA TEMA 8 KELAS IV SD 2 KARANGBENER BAE KUDUS TAHUN AJARAN 2020/2021 (JS (JURNAL SEKOLAH), 2021)
Abstract: The Increase in Study Results Students with Flipped classroom Model On the theme of 8 fourth grade of State Elementary Schools (SDN) 2 Karangbener Bae Kudus the school year 2020/2021. The general objective of this research is to provide a new innovation in learning activities that can improve student learning outcomes in elementary schools. The specific purpose of this study was to find out the improvement of learning outcomes in Theme 8 My Living Area using the Flipped Classroom model for fourth grade students at SD 2 Karangbener. The research subjects were the fourth grade students of SD 2 Karangbener, Bae District, Kudus Regency, totaling 13 students. Sources of data come from teachers and students. Data collection techniques with observation and tests. The results showed that the Flipped classroom model can improve student learning outcomes. Improved student learning outcomes can be from the results of the assessment carried out at the end of each cycle I, cycle II and cycle III. In the first cycle, there were 8 students who finished studying and 5 students did not finish learning. The percentage of classical learning completeness in the first cycle is 61.54% with an average value of 70.62. In cycle II, there were 10 students who had completed their studies and only 3 students who did not complete their studies. The percentage of classical learning completeness in the second cycle is 76.92% with an average grade of 77.92. Meanwhile, in the third cycle, there were 11 students who finished studying and only 2 students who did not complete their studies. The percentage of classical learning completeness in the third cycle is 84.62% with an average grade of 81.54Keyword : Study Results, Flipped classroom Model.Abstrak: Peningkatan Hasil Belajar Siswa melalui Model Flipped classroom Pada Tema 8 Kelas IV SD 2 Karangbener Bae Kudus Tahun Ajaran 2020/2021. Tujuan umum penelitian ini adalah memberikan suatu inovasi baru dalam kegiatan pembelajaran yang dapat meningkatkan hasil belajar siswa disekolah dasar. Tujuan khusus penelitian ini mengetahui peningkatan hasil belajar Tema 8 Daerah Tempat Tinggalku menggunakan model Flipped Classroom pada siswa kelas IV di SD 2 Karangbener. Penelitian ini dilakukan dalam 3 siklus. Subjek penelitian adalah siswa kelas IV SD 2 Karangbener Kecamatan Bae Kabupaten Kudus yang berjumlah 13 siswa. Sumber data berasal dari guru dan siswa. Teknik pengumpulan data dengan observasi dan tes. Hasil penelitian menunjukkan bahwa model Flipped classroom dapat meningkatkan hasil belajar siswa. Peningkatan hasil belajar siswa dapat dari hasil penilaian yang dilaksanakan pada akhir setiap siklus I, siklus II dan siklus III. Pada siklus I terdapat 8 siswa yang tuntas belajar dan 5 siswa tidak tuntas belajar. Persentase ketuntasan belajar klasikal pada siklus I yakni 61,54% dengan nilai rata-rata yakni 70,62. Pada siklus II terdapat 10 siswa yang tuntas belajar dan hanya 3 siswa yang tidak tuntas belajar. Persentase ketuntasan belajar klasikal pada siklus II yakni 76,92% dengan nilai rata-rata kelas yakni 77,92. Sedangkan pada siklus III terdapat 11 siswa yang tuntas belajar dan hanya 2 siswa yang tidak tuntas belajar. Persentase ketuntasan belajar klasikal pada siklus III yakni 84,62% dengan nilai rata-rata kelas yakni 81,54Kata kunci: Hasil Belajar, Model Flipped Classroom.